Enhancing elderly health examination effectiveness by adding physical function evaluations and interventions. (May 2017) - Li, Chia-Ming; Chang, Ching-I; Yu, Wen-Ruey; Yang, Winnie; Hsu, Chih-Cheng; Chen, Ching-Yu
Highlights: This study aimed to assess the benefit of adding physical function evaluations and interventions to routine elderly health examination. The intervention included functional evaluations, exercise instruction, and nutrition education. Adding functional evaluations and interventions to the annual elderly health examination appeared to benefit the health of adults aged 70 years and older. Abstract: This study aimed to assess the benefit of adding physical function evaluations and interventions to routine elderly health examination. This is a Quasi-experimental controlled trial. 404 elderly adults (aged 70 and over) scoring 3–6 on the Canadian Study of Health and Aging Clinical Frailty Scale Chinese In-Person Interview Version (CSHA-CFS) in a 2012 annual elderly health examination were enrolled. Both the control and experimental groups received the routine annual health examination with the latter further provided with functional evaluations, exercise instruction, and nutrition education. 112 (84.8%) persons in the experiment group and 267 (98.2%) in the control group completed the study. CSHA-CFS performance of the experimental group was more likely to improve (odds ratio = 9.50, 95% confidence interval (CI) = 4.62–19.56) and less likely to deteriorate (OR = 0.04, 95% CI = 0.01–0.31) one year after intervention. Within the experimental group, Fried Frailty Index improvement percentage surpassed the deterioration percentage (29.5% vs. 0.9%, p < 0.001), five-meter walk speed rose from 1.0 ± 0.2 to 1.2 ± 0.2 m/s (p < 0.001), grip strength escalated from 22.3 ± 7.1 to 24.8 ± 6.7 kg (p < 0.001), Short-form Physical Performance Battery increased from 10.0 ± 1.6 to 11.6 ± 0.9 (p < 0.001), and timed up and go test decreased from 10.9 ± 2.9 to 8.9 ± 2.7 s (p < 0.001). However, no statistical difference was detected in composite adverse endpoints, including hospitalization, emergency department visit and falls, between the two groups, though the incidence was higher in the control group. Adding functional evaluations, exercise and nutrition interventions to the annual elderly health examination appeared to benefit the health of adults aged 70 years and older.